58.0k views
1 vote
What substitution should be used to rewrite 6(x+5)^2+5(x+5)-4=0 as a quadratic equation

User Semjon
by
5.1k points

2 Answers

6 votes

Explanation:

6 (x+5 )^2 +5(x+5)-4=0

let x+5= y

6y^2 + 5y - 4=0

6y^2 + 8y - 3y-4 =0

2y (3y+4) - 1 (3y+4)=0

(2y-1)(3y+4)=0

2y-1=0 or 3y+4=0

y=1/3 or -4/3

Recall that x+5=y

When y=1/3

x+5=1/3

x= -14/3

when y= -4/3

x+5=-4/3

x = -11/3

User Harmeet
by
5.2k points
3 votes

Answer:

u=(x+5)

Explanation:

User Mohamed Elkamaly
by
5.6k points